The Effect of Circuit Training on Mawashi Geri's Kick Speed Results for Kumite Athletes at the KKNSI Dojo Don Bosco Disci College in 2020 - Indra Irianto; Rahman Situmeang (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
The purpose of this study was to determine the effect of circuit training training on the results of Mawashi Geri's kick speed in Kumite athletes Go to KKNSI Don Bosco Diski in 2020. The location of this research was carried out at Dojo Don Bosco Diski Catholic School Deli Murni Diski. When this research was conducted in July until August. The research method used in this research is the experimental method. The population was all athletes of the Don Bosco Diski Dojo totaling 26 people and the number of samples was 8 people obtained by simple random sampling technique. Research instrument for data collection. This research was conducted for 18 meetings with a frequency of training 4 (four) times a week. To see the effect of the independent and dependent variables, t-test calculations were used. With this research, it can provide accurate data about the effect of Circuit Training training on increasing Mawashi Geri's kick speed in the Don Bosco Diski Kumite Dojo athlete in 2020. The results of this study indicate that there is a significant effect of Circuit Training training on the improvement of Mawashi Geri's tendanga speed in Don Bosco Diski Kumite athletes with hypothesis analysis from the pre-test and post-test data, the results of the kick speed results obtained tcount = 11.80 and t table of = 1.86 with α = 0.05 (tcount> ttable) or (11.80> 1.86) means that Ho is rejected and Ha is accepted.